Iridium-cobalt oxide nanoparticles as well as preparation method and application thereof

By using iridium-cobalt oxide nanoparticles as OER reaction catalysts under acidic electrolytic water conditions, the problem of insufficient electrochemical performance and stability of existing Ir-based and Ru-based catalysts is solved, and the catalytic effect with high electrochemical activity and stability is achieved, which is suitable for industrial applications of hydrogen production by electrolytic water.

CN119593011APending Publication Date: 2025-03-11SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411886593.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing Ir-based catalysts and Ru-based catalysts have problems that the electrochemical properties need to be improved and the stability is poor under acidic electrolytic water conditions, which are difficult to meet the practical application requirements.

Method used

Iridium-cobalt oxide nanoparticles are used as the OER reaction catalyst, and nanoparticles with high electrochemical activity and stability are formed by doping tricobalt tetroxide support and iridium oxide and combining complex complexes with iridium-cobalt hydroxide.

Benefits of technology

It improves the electrochemical activity and stability of the catalyst, reduces the overpotential of the oxygen evolution reaction, and is suitable for industrial applications in the field of electrolyzed hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593011A_ABST
    Figure CN119593011A_ABST
Patent Text Reader

Abstract

The invention discloses iridium-cobalt oxide nanoparticles as well as a preparation method and application thereof. The iridium-cobalt oxide nanoparticles comprise a cobaltosic oxide carrier and supported iridium oxide. The preparation method comprises the following steps: 1) preparing an iridium salt-cobalt salt aqueous solution; 2) preparing a reaction solution of a complex containing iridium ammonium salt and cobalt; (3) preparing an iridium hydroxide-cobalt complex compound; and 4) grinding the iridium hydroxide-cobalt complex compound, placing the ground complex compound in an oxygen-containing atmosphere for heat treatment, and then carrying out water washing and drying. The iridium-cobalt oxide nano-particles are low in iridium content, small and uniform in particle size and simple in preparation method, have the advantages of being high in electrochemical activity, good in electrochemical stability and the like when being used as an OER reaction catalyst, and are suitable for large-scale industrial application in the field of hydrogen production through water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to iridium-cobalt oxide nanoparticles and a preparation method and application thereof. Background Art

[0002] The extremely slow regeneration rate of fossil fuels and the sustainability issues have prompted the global energy system to shift to renewable energy. Hydrogen energy is a green renewable energy with high energy density (energy density is 142MJ / kg, about 3 times that of oil / 4.5 times that of coal), and the product is carbon-free, which has broad practical application prospects. It is well known that the method of using electricity generated by renewable energy such as wind energy and solar energy to electrolyze water to produce hydrogen is an efficient and green hydrogen production method, and the development of low-cost water electrolysis hydrogen production equipment is the key.

[0003] Among various water electrolysis devices, acidic proton exchange membrane electrolyzer (PEM) has a broader application prospect due to its higher efficiency and shorter reaction time. The working environment of acidic proton exchange membrane electrolyzer is a strongly acidic environment, which poses a severe challenge to the catalysts of the cathode / anode. At present, the catalysts used in the cathode / anode are mostly precious metals (such as Pt, Ir, Ru, etc.) that can exist relatively stably in a strongly acidic environment (for example: commercial water electrolysis cathode reaction catalyst is mainly Pt / C catalyst, while the anode reaction catalyst is mainly Ir, Ru element / oxide). In the process of water electrolysis, oxygen evolution reaction (OER) will occur at the anode and hydrogen evolution reaction (HER) will occur at the cathode. The HER reaction is a 2-electron transfer reaction, while the OER reaction is a 4-electron transfer reaction, so the OER reaction often requires additional voltage to drive it, and finally it can complete the entire water electrolysis process. Studies have shown that the Pt loading of Pt-based catalysts only needs to reach 0.025mg / cm 2 ~0.3mg / cm 2 The Ir loading of Ir-based catalysts needs to be at least 2 mg / cm 2 Only in this way can the OER reaction be promoted. Therefore, the efficiency of the OER reaction at the anode determines the efficiency of the PEM electrolysis device.

[0004] At present, most of the catalysts used under acidic water electrolysis conditions are modified and designed based on Ir-based catalysts and Ru-based catalysts. Ir-based catalysts have high stability, but their electrochemical performance needs to be further improved. Ru-based catalysts usually show better electrochemical performance than Ir-based catalysts, but Ru-based catalysts will be oxidized and dissolved when the voltage increases, and their stability is poor. In summary, the existing Ir-based catalysts and Ru-based catalysts have obvious defects and are difficult to fully meet the requirements of practical applications.

[0005] Therefore, it is of great significance to develop an OER reaction catalyst with high electrochemical activity and good electrochemical stability. Summary of the invention

[0006] The purpose of the present invention is to provide iridium-cobalt oxide nanoparticles and a preparation method and application thereof.

[0007] The technical solution adopted by the present invention is:

[0008] The invention discloses iridium-cobalt oxide nanoparticles, which are composed of a cobalt tetraoxide carrier and supported iridium oxide.

[0009] Preferably, the molar ratio of iridium to cobalt in the iridium-cobalt oxide nanoparticles is 1:0.1-0.5.

[0010] Preferably, the average particle size of the iridium-cobalt oxide nanoparticles is 2 nm to 3 nm.

[0011] A method for preparing the iridium-cobalt oxide nanoparticles as described above comprises the following steps:

[0012] 1) preparing an iridium salt-cobalt salt aqueous solution;

[0013] 2) adding ammonia water to the iridium salt-cobalt salt aqueous solution to adjust the pH value of the solution to 7.5-8.5 and then reacting to obtain a reaction solution containing an ammonium salt of iridium and a complex of cobalt;

[0014] 3) adding sodium hydroxide to the reaction solution containing the ammonium salt of iridium and the cobalt complex to adjust the pH value of the solution to 11-13, and then reacting, and then removing the solvent to obtain an iridium hydroxide-cobalt complex;

[0015] 4) Grinding the iridium hydroxide-cobalt complex, placing it in an oxygen-containing atmosphere for heat treatment, and then washing and drying it to obtain iridium-cobalt oxide nanoparticles.

[0016] Preferably, the iridium salt in step 1) is at least one of IrCl3, H2IrCl6, and IrCl4.

[0017] Preferably, the cobalt salt in step 1) is at least one of CoCl2 and Co(NO3)2.

[0018] Preferably, the reaction time in step 2) is 1 h to 2 h.

[0019] Preferably, the reaction time in step 3) is 1 h to 2 h.

[0020] Preferably, the method of removing the solvent in step 3) is freeze drying, and the freeze drying is carried out at a temperature of -60°C to -40°C, and the drying time is 12h to 24h.

[0021] Preferably, the oxygen-containing atmosphere in step 4) is an air atmosphere.

[0022] Preferably, the heat treatment in step 4) comprises the following operations: firstly controlling the heating rate to be 1°C / min to 3°C / min from room temperature (25°C±5°C) to 300°C to 600°C, and then keeping the temperature for 1h to 4h.

[0023] An oxygen evolution reaction catalyst comprises the iridium-cobalt oxide nanoparticles.

[0024] An application of the iridium-cobalt oxide nanoparticles as described above in producing hydrogen by electrolysis of water.

[0025] The beneficial effects of the present invention are as follows: the iridium-cobalt oxide nanoparticles of the present invention have a low iridium content, a small and uniform particle size, and a simple preparation method. When used as an OER reaction catalyst, they have the advantages of high electrochemical activity and good electrochemical stability, and are suitable for large-scale industrial application in the field of hydrogen production by electrolysis of water.

[0026] Specifically:

[0027] 1) The present invention uses cobalt tetroxide to dope iridium oxide, so that iridium oxide can still maintain a stable structure under high potential, thereby improving the stability of the catalyst;

[0028] 2) The present invention utilizes cobalt tetroxide to dope iridium oxide, which not only improves the catalytic activity of the catalyst, but also effectively improves the stability of the catalyst after long-term use and reduces the overpotential of the oxygen evolution reaction;

[0029] 3) The present invention allows the reaction to occur step by step by successively adding different alkaline substances. The step-by-step treatment can make the iridium hydroxide loading on the carrier more uniform, and then heat treatment is performed in an oxygen-containing atmosphere to form a transition metal oxide-doped nanocatalyst. The particle size of the catalyst finally obtained is more uniform, the particle size is smaller, and the catalytic activity is more excellent;

[0030] 4) The preparation method of the iridium-cobalt oxide nanoparticles of the present invention is simple, requires less raw materials, and the operating conditions are easy to achieve, and is suitable for large-scale preparation and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 TEM and SEM images of the iridium-cobalt oxide nanoparticles in Example 1.

[0032] Figure 2Steady-state polarization curves of the iridium-cobalt oxide nanoparticles in Examples 1 to 3 and the commercial IrO2 catalyst.

[0033] Figure 3 CV curves of the iridium-cobalt oxide nanoparticles in Example 1 and the commercial IrO2 catalyst.

[0034] Figure 4 This is a 2 h chronoamperometry stability comparison chart of the iridium-cobalt oxide nanoparticles in Example 1 and the commercial IrO2 catalyst.

[0035] Figure 5 This is a 10 h chronovoltametry stability comparison chart of the iridium-cobalt oxide nanoparticles in Example 1 and the commercial IrO2 catalyst. DETAILED DESCRIPTION

[0036] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0037] Embodiment 1:

[0038] An iridium-cobalt oxide nanoparticle, the preparation method of which is as follows:

[0039] 1) Add 141 mg (0.4 mmol) of IrCl3·3H2O and 13 mg (0.1 mmol) of CoCl2 into 20 mL of deionized water, dissolve and stir at room temperature for 30 min to obtain an iridium salt-cobalt salt aqueous solution;

[0040] 2) adding 10% ammonia water to the iridium salt-cobalt salt aqueous solution to adjust the pH value of the solution to 8, stirring at room temperature for 1 hour to obtain a reaction solution containing an iridium ammonium salt and a cobalt complex;

[0041] 3) adding a sodium hydroxide solution having a concentration of 0.5 mol / L to the reaction solution containing the ammonium salt of iridium and the cobalt complex to adjust the pH value of the solution to 12, stirring at room temperature for 1 hour, and then placing it at -50°C and vacuum drying for 20 hours to obtain an iridium hydroxide-cobalt complex (black powder);

[0042] 4) The iridium hydroxide-cobalt complex is ground, loaded into a porcelain boat and placed in a tubular furnace. The temperature is raised from room temperature to 350°C at a heating rate of 2°C / min under an air atmosphere, then kept at this temperature for 2 hours, cooled naturally to room temperature, and the calcined product is washed with water, filtered and dried to obtain iridium-cobalt oxide nanoparticles.

[0043] Performance Testing:

[0044] 1) The transmission electron microscope (TEM) and scanning electron microscope (SEM) images of the iridium-cobalt oxide nanoparticles in this embodiment are as follows: Figure 1(a is TEM image, b is SEM image).

[0045] Depend on Figure 1 It can be seen that the iridium-cobalt oxide nanoparticles in this embodiment have good dispersibility and low crystallinity. Nanoparticles are randomly selected and the particle size is measured in the TEM image to obtain the particle size distribution of the nanoparticles. The average particle size of the nanoparticles is 2.7 nm, which is smaller than that of the commercial IrO2 catalyst (Duralyst, USA, with an average particle size of 4.1 nm) (generally speaking, the smaller the particle size of the catalyst, the better the catalytic activity. Therefore, the iridium-cobalt oxide nanoparticles in this embodiment have higher electrochemical activity than the commercial IrO2 catalyst).

[0046] 2) The iridium-cobalt oxide nanoparticles in this embodiment and the commercial IrO2 catalyst (Duralyst from the United States, with an average particle size of 4.1 nm) were dispersed in an isopropanol-water mixed solvent (the volume ratio of isopropanol to water was 3:2), and then coated on the surface of a rotating disk electrode (glassy carbon electrode), and then completely dried at 50°C to prepare a rotating disk electrode loaded with the catalyst (the catalyst loading was 30 μg / cm 2 ), and then immerse the rotating disk electrode loaded with the catalyst into an acidic electrolyte (H2SO4 solution with a concentration of 0.5 mol / L, saturated with oxygen at a constant temperature of 25°C), and then adjust the speed of the rotating disk electrode to 1600 rpm, and perform an OER electrochemical test (LSV test) on the catalyst from a low potential to a high potential at a scanning rate of 5 mV / s, with a scanning range of 1.2 V to 1.8 V vs. RHE. The steady-state polarization curve is shown in the figure Figure 2 shown.

[0047] Depend on Figure 2 It can be seen that according to the normalized calculation of the catalyst area mass activity, the iridium-cobalt oxide nanoparticles in this embodiment have a high intrinsic catalytic activity under the LSV test; at a current density of 10 mA / cm 2 The overpotential of the commercial IrO2 catalyst is 365 mV and the mass activity is 0.36 A / mg. IrO2 @1.6V vs. RHE, while the overpotential of the iridium-cobalt oxide nanoparticles in this example is 301mV and the mass activity is 1.31A / mg IrO2 @1.6V vs.RHE, the iridium-cobalt oxide nanoparticles in this embodiment have higher mass activity and smaller overpotential, indicating that the electrochemical activity of the iridium-cobalt oxide nanoparticles in this embodiment is more excellent.

[0048] 3) Cyclic voltammetry scanning was performed on the iridium-cobalt oxide nanoparticles and commercial IrO2 catalyst (Duralyst, USA, with an average particle size of 4.1 nm) in this embodiment. The electrode processing steps and the process of loading onto the glassy carbon electrode were the same as the above-mentioned LSV test process. During the test, the scanning range was 0.87V to 0.97V, the rotation speed of the rotating disk electrode was adjusted to 1600rpm, and scanning was performed at different scanning rates of 10mV / s, 20mV / s, 30mV / s, 40mV / s and 50mV / s. The CV curves obtained are as follows: Figure 3 (a is iridium-cobalt oxide nanoparticles, b is commercial IrO2 catalyst) as shown.

[0049] Depend on Figure 3 It can be seen that the electrochemical active area of ​​the iridium-cobalt oxide nanoparticles in this embodiment is 101.4 m 2 / g, while the electrochemical active area of ​​commercial IrO2 catalyst is 74.0 m 2 / g, the electrochemical active area of ​​the iridium-cobalt oxide nanoparticles in this embodiment is significantly improved compared with the commercial IrO2 catalyst, indicating that the iridium-cobalt oxide nanoparticles in this embodiment have better electrochemical performance than the commercial IrO2 catalyst.

[0050] 4) The stability of the iridium-cobalt oxide nanoparticles in this embodiment and the commercial IrO2 catalyst (Duralyst from the United States, with an average particle size of 4.1 nm) was evaluated by chronoamperometry. The specific test method was the same as the steady-state polarization curve determination step, that is, the temperature was kept constant and oxygen was saturated, and then the current was kept constant at 0.00196 A, the speed of the rotating disk electrode was adjusted to 1600 rpm, and the voltage response to the electrode scanning time was recorded for 2 h. The 2 h chronoamperometry stability comparison was obtained. Figure 4 (a is a stability comparison diagram, b is the steady-state polarization curve after 2h testing).

[0051] Depend on Figure 4 It can be seen that the steady-state polarization curve of the iridium-cobalt oxide nanoparticles in this embodiment is relatively gentle. After 2 hours of testing, the overpotential is only 321mV, and the mass activity is 1.03A / mg. IrO2 @1.6V vs. RHE, the overpotential increased by only 19mV and the mass activity lost only 22%, while the commercial IrO2 catalyst had an overpotential of 435mV and a mass activity of 0.091A / mg after 2h of testing. IrO2@1.6V vs.RHE, the overpotential increased by 70mV and the mass activity lost by 75%, indicating that the iridium-cobalt oxide nanoparticles in this embodiment exhibited better electrochemical durability than the commercial IrO2 catalyst, and had better electrochemical oxygen evolution performance than the commercial IrO2 catalyst under acidic conditions.

[0052] 5) The stability of the iridium-cobalt oxide nanoparticles and the commercial IrO2 catalyst (Duralyst, USA, with an average particle size of 4.1 nm) in this embodiment was evaluated by the chronovoltametry. The specific test method was the same as the steady-state polarization curve determination step, that is, the temperature was kept constant and oxygen was saturated, and then the voltage was kept constant at 1.5 V. The speed of the rotating disk electrode was adjusted to 1600 rpm, and the response of the current density to the electrode scanning time was recorded. The recording time was 10 h. The stability comparison of the 10 h chronovoltametry was obtained. Figure 5 (a is a stability comparison diagram, b is the steady-state polarization curve after 10h testing).

[0053] Depend on Figure 5 It can be seen that the overpotential of the iridium-cobalt oxide nanoparticles in this embodiment is only 314 mV after 10 hours of testing, and the mass activity is 1.08 A / mg IrO2 @1.6V vs.RHE, the overpotential increased by only 12mV and the loss of mass activity was only 17.5% compared with before the test. However, the overpotential of the commercial IrO2 catalyst increased to 399mV after 10h of testing, and the mass activity was 0.147A / mg IrO2 @1.6V vs.RHE, the overpotential increased by 34mV and the mass activity lost by 59% compared with that before the test, indicating that the iridium-cobalt oxide nanoparticles in this embodiment exhibited better electrochemical durability than the commercial IrO2 catalyst, and had better electrochemical oxygen evolution performance than the commercial IrO2 catalyst under acidic conditions.

[0054] Embodiment 2:

[0055] An iridium-cobalt oxide nanoparticle, the preparation method of which is as follows:

[0056] 1) Add 162.78 mg (0.4 mmol) of H2IrCl6·6H2O and 13 mg (0.1 mmol) of CoCl2 into 20 mL of deionized water, dissolve and stir at room temperature for 30 min to obtain an iridium salt-cobalt salt aqueous solution;

[0057] 2) adding 10% ammonia water to the iridium salt-cobalt salt aqueous solution to adjust the pH value of the solution to 8, stirring at room temperature for 1 hour to obtain a reaction solution containing an iridium ammonium salt and a cobalt complex;

[0058] 3) adding a sodium hydroxide solution having a concentration of 0.5 mol / L to the reaction solution containing the ammonium salt of iridium and the cobalt complex to adjust the pH value of the solution to 12, stirring at room temperature for 1 hour, and then placing it at -50°C and vacuum drying for 20 hours to obtain an iridium hydroxide-cobalt complex (black powder);

[0059] 4) The iridium hydroxide-cobalt complex is ground, loaded into a porcelain boat and placed in a tubular furnace. The temperature is raised from room temperature to 350°C at a heating rate of 2°C / min under an air atmosphere, then kept at this temperature for 2 hours, cooled naturally to room temperature, and the calcined product is washed with water, filtered and dried to obtain iridium-cobalt oxide nanoparticles.

[0060] The steady-state polarization curve of the iridium-cobalt oxide nanoparticles in this embodiment is as follows: Figure 2 shown.

[0061] Depend on Figure 2 It can be seen that the iridium-cobalt oxide nanoparticles in this embodiment have a current density of 10 mA / cm 2 At, the overpotential is 308mV and the mass activity is 1.27A / mg IrO2 @1.6V vs RHE, indicating that it has higher activity than commercial IrO2 catalyst.

[0062] In addition, it was found through testing (the testing method was the same as that of Example 1) that the iridium-cobalt oxide nanoparticles in this example also had excellent electrochemical durability.

[0063] Embodiment 3:

[0064] An iridium-cobalt oxide nanoparticle, the preparation method of which is as follows:

[0065] 1) Add 141 mg (0.4 mmol) of IrCl3·3H2O and 18 mg (0.1 mmol) of Co(NO3)2 into 20 mL of deionized water, dissolve and stir at room temperature for 30 min to obtain an iridium salt-cobalt salt aqueous solution;

[0066] 2) adding 0.3 mol / L ammonia water to the iridium salt-cobalt salt aqueous solution to adjust the pH value of the solution to 8, stirring at room temperature for 1 hour to obtain a reaction solution containing an iridium ammonium salt and a cobalt complex;

[0067] 3) adding a sodium hydroxide solution having a concentration of 0.5 mol / L to the reaction solution containing the ammonium salt of iridium and the cobalt complex to adjust the pH value of the solution to 12, stirring at room temperature for 1 hour, and then placing it at -50°C and vacuum drying for 20 hours to obtain an iridium hydroxide-cobalt complex (black powder);

[0068] 4) The iridium hydroxide-cobalt complex is ground, loaded into a porcelain boat and placed in a tubular furnace. The temperature is raised from room temperature to 350°C at a heating rate of 2°C / min under an air atmosphere, then kept at this temperature for 2 hours, cooled naturally to room temperature, and the calcined product is washed with water, filtered and dried to obtain iridium-cobalt oxide nanoparticles.

[0069] The steady-state polarization curve of the iridium-cobalt oxide nanoparticles in this embodiment is as follows: Figure 2 shown.

[0070] Depend on Figure 2 It can be seen that the iridium-cobalt oxide nanoparticles in this embodiment have a current density of 10 mA / cm 2 At, the overpotential is 312mV and the mass activity is 1.191A / mg IrO2 @1.6 V vs RHE (slightly lower activity than the iridium-cobalt oxide nanoparticles in Example 1), indicating that it has higher activity than the commercial IrO2 catalyst.

[0071] In addition, it was found through testing (the testing method was the same as that of Example 1) that the iridium-cobalt oxide nanoparticles in this example also had excellent electrochemical durability.

[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An iridium-cobalt oxide nanoparticle, characterized in that: The composition comprises a cobalt tetraoxide carrier and supported iridium oxide.

2. The iridium-cobalt oxide nanoparticles according to claim 1, characterized in that: The molar ratio of iridium to cobalt in the iridium-cobalt oxide nanoparticles is 1:0.1-0.

5.

3. The iridium-cobalt oxide nanoparticles according to claim 1 or 2, characterized in that: The average particle size of the iridium-cobalt oxide nanoparticles is 2nm-3nm.

4. A method for preparing iridium-cobalt oxide nanoparticles according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) preparing an iridium salt-cobalt salt aqueous solution; 2) adding ammonia water to the iridium salt-cobalt salt aqueous solution to adjust the pH value of the solution to 7.5-8.5 and then reacting to obtain a reaction solution containing an ammonium salt of iridium and a complex of cobalt; 3) adding sodium hydroxide to the reaction solution containing the ammonium salt of iridium and the cobalt complex to adjust the pH value of the solution to 11-13, and then reacting, and then removing the solvent to obtain an iridium hydroxide-cobalt complex; 4) Grinding the iridium hydroxide-cobalt complex, placing it in an oxygen-containing atmosphere for heat treatment, and then washing and drying it to obtain iridium-cobalt oxide nanoparticles.

5. The preparation method according to claim 4, characterized in that: The iridium salt in step 1) is at least one of IrCl3, H2IrCl6, and IrCl4; the cobalt salt in step 1) is at least one of CoCl2 and Co(NO3)2.

6. The preparation method according to claim 4 or 5, characterized in that: The reaction time of step 2) is 1 h to 2 h.

7. The preparation method according to claim 4 or 5, characterized in that: Step 3) The reaction time is 1 h to 2 h.

8. The preparation method according to claim 4 or 5, characterized in that: Step 4) The heat treatment includes the following operations: firstly control the heating rate to be 1°C / min to 3°C / min from room temperature to 300°C to 600°C, and then keep the temperature for 1h to 4h.

9. An oxygen evolution reaction catalyst, characterized in that: The invention comprises the iridium-cobalt oxide nanoparticles according to any one of claims 1 to 3.

10. Use of the iridium-cobalt oxide nanoparticles according to any one of claims 1 to 3 in producing hydrogen by electrolysis of water.

Citation Information

Cited By

  • PEM water electrolysis catalyst, PEM water electrolysis oxygen desorption electrode and preparation method and application of PEM water electrolysis catalyst and PEM water electrolysis oxygen desorption electrode

    CN120700528A